The Dialectics of Text and Reason: Badr al-Dīn al-Zarkashī's Contribution to Qur’anic Interpretive Methodology in the 8th Century Hijriyah - Maqdis; Rizqotul Luqi Mufidah (Basmala: Journal of Qur’an and Hadith, 2025)
This research comprehensively analyzes the methodological framework of Qur’anic interpretation according to Badr ad-Dīn az-Zarkasyi, as outlined in al-Burhān  fī ʿUlūm al-Qurʾān. The study aims to fill a gap in the literature that often overlooks the legitimacy of raʾy (reason/ijtihād) in al-Zarkashī’s methodology, especially in light of the general perception regarding the dominance of the transmissive-static approach in Sunni exegesis during the 8th century Hijri. Using Gadamer’s hermeneutic framework, this research carefully explores how al-Zarkashīcategorizes the verses of the Qur’an, identifies the sources of his interpretations, and formulates the mechanism of ijtihād as a fundamental and legitimate tool for meaning-making. From a deep analysis, a crucial finding emerged: al-Zarkashī explicitly distinguishes between interpretation based on narration and taʾwīl that involves ijtihād, opening significant space for the use of reason for verses that do not have a definitive interpretation (qath’i). He emphasizes the necessity of ijtihād so that the Qur’an can continuously engage in dialectics with the dynamics of the times (tanazzul), even daring to reinterpret hadiths that are often misunderstood as prohibitions against raʾy with strong arguments. The methodology of ijtihād that he advocates is very solid, deeply rooted in the mastery of Arabic linguistic knowledge and uṣūl al-fiqh (principles of Islamic jurisprudence). This finding not only enriches the “big picture” of the history of Sunni exegesis in the medieval period by demonstrating that the philological-dialectical model accommodating raʾy (opinion) remains significant, but it also positions al-Zarkashī as an important figure who successfully bridges tradition and progressiveness in the realm of Islamic interpretative thought [Penelitian ini menganalisis secara komprehensif kerangka metodologis penafsiran al-Qur’an menurut Badr ad-Dīn al-Zarkashī sebagaimana tertulis dalam al-Burhān fī ʿUlūm al-Qurʾān. Kajian ini berupaya mengisi celah dalam literatur yang seringkali kurang menyoroti secara mendalam legitimasi raʾy (rasio/ijtihād) dalam metodologi al-Zarkashī, terutama di tengah pandangan umum mengenai dominasi pendekatan transmitif-statis dalam tafsir Sunni pada abad ke-8 Hijriah. Dengan menggunakan kerangka hermeneutika Gadamer, penelitian ini menelusuri secara cermat bagaimana al-Zarkashī mengkategorikan ayat-ayat Al-Qur’an, mengidentifikasi sumber-sumber interpretasinya, dan merumuskan mekanisme ijtihād sebagai alat pemaknaan yang fundamental dan sah. Dari analisis mendalam, terungkap sebuah temuan krusial: al-Zarkashī secara eksplisit membedakan antara tafsir yang berbasis riwayat dan taʾwīl yang melibatkan ijtihād, membuka ruang signifikan bagi penggunaan rasio untuk ayat-ayat yang belum memiliki penafsiran yang qath'i. Ia menegaskan perlunya ijtihād agar Al-Qur’an senantiasa berdialektika dengan dinamika zaman (tanazzul), bahkan berani mereinterpretasi hadis-hadis yang sering disalahpahami sebagai pelarangan raʾy dengan argumen yang kokoh. Metodologi ijtihād yang ia usung sangat solid, berakar kuat pada penguasaan ilmu kebahasaan Arab dan uṣūl al-fiqh. Temuan ini tidak hanya memperkaya “peta besar” sejarah tafsir Sunni abad pertengahan dengan menunjukkan bahwa model filologis-dialektis yang akomodatif terhadap raʾy tetap signifikan, tetapi juga menempatkan al-Zarkashī sebagai figur penting yang berhasil menjembatani tradisi dan progresivitas dalam khazanah pemikiran interpretatif Islam.]